2015
DOI: 10.1103/physreva.92.013631
|View full text |Cite
|
Sign up to set email alerts
|

Few-fermion systems in one dimension: Ground- and excited-state energies and contacts

Abstract: Using the lattice Monte Carlo method, we compute the energy and Tan's contact in the ground state as well as the first excited state of few-to many-fermion systems in a one-dimensional periodic box. We focus on unpolarized systems of N = 4, 6, ..., 12 particles, with a zero-range interaction, and a wide range of attractive couplings. In addition, we provide extrapolations to the infinite-volume and thermodynamic limits.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
29
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(36 citation statements)
references
References 52 publications
7
29
0
Order By: Relevance
“…In particular, we compare our results to those previously obtained with HMC in Ref. [13] for attractive systems which have also been found to agree with exact results from the Bethe ansatz. Additionally, we show results from a renormalization-group approach to density functional theory based on the microscopic interactions defining our model [51].…”
Section: Mass Balanced Case: Arbitrary Interactionsupporting
confidence: 75%
“…In particular, we compare our results to those previously obtained with HMC in Ref. [13] for attractive systems which have also been found to agree with exact results from the Bethe ansatz. Additionally, we show results from a renormalization-group approach to density functional theory based on the microscopic interactions defining our model [51].…”
Section: Mass Balanced Case: Arbitrary Interactionsupporting
confidence: 75%
“…the ground state energy of this system in the zero-temperature limit is given by the (N ↑ + N ↓ )/2 times the binding energy of the associated two-body bound state (see, e.g., Refs. [8,[28][29][30]). Thus, even in the limit of small dimensionless couplingḡ, bound states are formed.…”
Section: A Pairing Effectsmentioning
confidence: 99%
“…Such oscillations are typically associated with so-called shell effects and have been seen in 1D and 3D analogues of this system (see e.g. [51] and [52]). In order to better understand the strong coupling regime, we N ε F .…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, it has been shown that C controls the high-momentum tail of the momentum distribution (see below) [54], as well as multiple sum rules of real-time response functions [55]. The calculation of C itself, however, involves a many-body problem that requires computational approaches [51,56]. The contact obeys an adiabatic theorem (see [57,58] (1), the scattering length enters fully through the bare coupling g (and, of course, the UV lattice cutoff, which we hold constant).…”
Section: Resultsmentioning
confidence: 99%